An intriguing convergence between metaverse and sustainable human resource management - Aanyaa Chaudhary; Sonal Khandelwal; Pankaj Deshpande; Poonam Panjabi (SA Journal of Human Resource Management)
Orientation: This research aims to shed light on emerging trends, key themes and future directions in the nascent field of the metaverse and sustainable human resource management (HRM).